Leaf application of silicic acid to upland rice and corn - Costa Crusciol, Carlos Alexandre [UNESP]; Soratto, Rogério Peres [UNESP]; Amaral Castro, Gustavo Spadotti; Ferrari Neto, Jayme [UNESP]; Martins da Costa, Claudio Hideo [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
This study aimed to evaluate the effect of Si (stabilized silicic acid, Silamol (R)) leaf application on mineral nutrition and yield in upland rice and corn crops. The treatments were the control (without Si) and Si foliar split spraying using 2 L ha(-1) of the Silamol (R) commercial product, with 0.8% soluble Si as concentrated stabilized silicic acid. Silicon leaf application increased the concentrations of K, Ca and Si in rice and corn leaves, the number of panicles per m(2) of rice and the number of grains per ear of corn; accordingly, the Si leaf application provided a higher grain yield in both crops.
Keywords: Oryza sativa; Zea mays; silicon; leaf fertilization; mineral nutrition